The Implementation of Quality Standards and Quality Objectives in Educational Institutions - Afriantoni; Saputra, Arya Yoga; Haikal, Haikal; Khatimah, Husnul (El-Idare: Journal of Islamic Education Management, 2025)
To realize the educational goals that have been set through the vision and mission of educational institutions, as well as to maintain and improve the quality of education in these institutions, effective implementation of quality standards and quality targets is required. Without clear quality standards and targets, educational institutions will lose direction and guidance in creating the expected quality. This study aims to understand the implementation of quality standards and targets in educational institutions. The method used is a literature review approach, which will provide an overview of the importance of implementing quality standards in education. Quality standards are benchmarks used to assess the performance and quality of educational institutions that include various aspects such as input, process, output, and existing outcomes. Quality targets are goals that educational institutions want to achieve through all processes carried out, both in the short and long term. In formulating quality targets, it is important to use the SMART approach, namely: Specific, Measurable, Achievable, Relevant, and Time Bound. With this approach, educational institutions can set clear and measurable goals, and ensure the achievement of targets within a specified time. This will help educational institutions to improve quality and achieve better and more focused educational goals, so that it can have a positive impact on the development of educational institutions and fulfill the needs of students and society as a whole.